MORINGA TECHNOLOGY BY USE OF MORINGA OLEIFERA AS BIO-COAGULENT - MR. YOGENDRA VIJAY BACHHAV (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Many undeveloped countries are still facing the problems with availability of uncontaminated drinking water due to several reasons like lack of knowledge, budget and resources. Chemical coagulants like Aluminum Sulphate (Alum), Ferric Sulphate (FeCl2) is used in waste water treatment plant. This excess use of chemical coagulants is hazardous to human health. Use of Bio-coagulant is need for today’s time. One of these there is alternative natural coagulant is moringa oleifera seeds. Moringa Oleifera is a perfect example of multipurpose tree. It has been found that Moringa to be non- toxic and recommended is to use as coagulant in treatment plant. The use of Moringa has an added as advantages over the chemical treatment of water.